Increased weighting on prior knowledge in Lewy body-associated visual hallucinations. Issue 1 (16th July 2019) - Zarkali, Angeliki; Adams, Rick A; Psarras, Stamatios; Leyland, Louise-Ann; Rees, Geraint; Weil, Rimona S
Abstract : The mechanisms of visual hallucinations in Lewy body disease are unknown. Zarkali et al. use two-tone stimuli to show that Lewy body hallucinations are associated with altered integration of top-down predictions with sensory evidence. Specifically, results show an increased relative weighting of prior knowledge in Lewy body hallucinations providing important mechanistic insights. Abstract: Hallucinations are a common and distressing feature of many psychiatric and neurodegenerative conditions. In Lewy body disease, visual hallucinations are a defining feature, associated with worse outcomes; yet their mechanisms remain unclear and treatment options are limited. Here, we show that hallucinations in Lewy body disease are associated with altered integration of top-down predictions with incoming sensory evidence, specifically with an increased relative weighting of prior knowledge. We tested 37 individuals with Lewy body disease, 17 habitual hallucinators and 20 without hallucinations, and 20 age-matched healthy individuals. We employed an image-based learning paradigm to test whether people with Lewy body disease and visual hallucinations show higher dependence on prior knowledge. We used two-tone images that are difficult to disambiguate without any prior information but generate a strong percept when information is provided. We measured discrimination sensitivity before and after this information was provided. We observed that in people with Lewy body disease who experience hallucinations, there was greater improvement in discrimination sensitivity after information was provided, compared to non-hallucinators and controls. This suggests that people with Lewy body disease and hallucinations place higher relative weighting on prior knowledge than those who do not hallucinate. Importantly, increased severity of visual hallucinations was associated with an increased effect of prior knowledge. Together these findings suggest that visual hallucinations in Lewy body disease are linked to a shift towards top-down influences on perception and away from sensory evidence, perhaps due to an increase in sensory noise. This provides important mechanistic insights to how hallucinations develop in Lewy body disease, with potential for revealing new therapeutic targets. Graphical Abstract: